Incidental finding of an accessory pronator during anterior transposition of the ulnar nerve with anterior interosseous nerve supercharge transfer: a case report - Mahapatra, Swagat; Pasricha, Navbir; Dwivedi, Alok Kumar; Beri, Sudhir; Gupta, Animesh; Kumar, Akshay (International Journal of Research in Orthopaedics, 2025)
The anterior transposition of the ulnar nerve with anterior interosseous nerve (AIN) supercharge transfer is a well-established procedure for improving motor recovery in severe ulnar neuropathy. Anatomical variations in the forearm musculature, such as the presence of an accessory pronator muscle, can have surgical and clinical implications. A 54-year-old female with cubital tunnel syndrome presented with progressive ulnar nerve dysfunction, including intrinsic muscle weakness and sensory deficits. She underwent anterior transposition of the ulnar nerve with AIN supercharge transfer. During the procedure, an unexpected accessory pronator muscle was identified between the pronator quadratus (PQ) and flexor digitorum profundus (FDP). The AIN innervated the muscle and was carefully dissected to facilitate nerve transfer. Postoperatively, the patient demonstrated improved intrinsic muscle strength without complications. Accessory muscles in the forearm are rare but may contribute to nerve compression syndromes or impact surgical approaches. This case highlights the importance of recognizing such anatomical variations to optimize surgical technique and avoid iatrogenic injury. Awareness of accessory pronators is crucial in upper limb nerve surgeries to ensure successful nerve transfer and prevent intraoperative complications.